Pattern-Based Layout Specifications for Visual Language Editors - Maier, Sonja; Minas, Mark (Electronic Communications of the EASST, 2010)
When creating an editor for a visual language, a challenging task is the layout specification. Many visual languages, e.g., Ecore diagrams or Petri nets, show similar layout characteristics, and hence reuse of layout behavior should be enabled. For that purpose, we introduce the concept of layout patterns, which encapsulates certain layout behavior. With the approach, it is possible to combine different layout algorithms, e.g., standard graph drawing algorithms and constraint-based algorithms. In addition, rule-based layout algorithms may be used that are specifically tailored to the interactive nature of visual language editors.